Perubahan Sosial Pada Komunitas Suku Bajo Di Pesisir Teluk Tomini - Muhammad Obie (AL-TAHRIR, 2016)
Abstract: Society and culture of human being always change as an ever –present phenomena in the world. A distinction is sometimes made then between processes of change within the social structure, which serve in part to maintain the structure, and, even the processes itself can be slow or fast through evolusion and revolusion.   One of the factors that quicken the social change process is the government interventions. This study aims at analyzing the social change on the Bajo Tribe community as the impact of various government programs at Tomini bay coastal. This research used strategy of historical sociology. The kinds of data collected were primer and secondary data that were analyzed by using qualitative approac. The result showed that various   government programs at Tomini bay, such as designating conservation area, granting concession license to private sectors through forest concession right (FCR)), indefeasible right of use (IRU), and fishing industry at the bay had caused the loss of access of the Bajo tribe community to coastal and marine resources area. Various interventions of government programs had implication on resettlement of the Bajo tribe community, causing the Bajo tribe divided into sea Bajo and land Bajo. The loss of access of the Bajo tribe to coastal and marine resources caused traditional institution weaken which made its philosophy of living in harmony with nature, and  conservation ethics fade away, its local wisdom, and self identity lose, and its social capital destructed.  الملخص: كان المجتمع وحضارته متغيّرين في أيّ كان المجتمع وهذه الحضارة. ويكون الفرق في كون هذا التغيّر. قد تكون عملية التغيّر متمهّلة أو سريعة وقد تكون عن طريق التطوّر والثّورة. وأحد العناصر المسرعة في عملية هذا التغيّر هو تدخّل الحكومة. حاولت هذه الدراسة تحليل التغيّر الاجتماعي في قبيلة "باجو" نتيجة لتطبيق البرامج الحكومية في سواحل خليج توميني. استخدمت هذه الدراسة الأسلوب الاجتماعي التاريخي. والبيانات المحصولة عليها في شكل البيانات الأولية والبيانات الثانوية ويكون تحليل البيانات بالمدخل الكيفي. دلّت نتائج البحث على أن البرامج المتنوّعة من الحكومة في ساحل خليج توميني في شكل اثبات مناطق الحفاظ، وتسليم الإذن لعملية الحفاظ تجاه الشركات الأهلية عن طريق HPH وHGU و تربية الأسماك (بركة الأسماك)، وأدت هذه البرامج إلى ضياع فرصة الاستفادة لقبيلة باجو تجاه الموارد السواحلية والبحرية. وتدخّل برامج الحكومة أدى إلى إعادة توطين مجتمع باجو وتفريقهم إلى مجتمع باجو البحري ومجتمع باجو البرّيّ.  وضياع فرصة الاستفادة لمجتمع باجو تجاه موارد الطاقات السواحلية والبحرية أدّى إلى ضعف المؤسسات التقاليدية وأدّى هذا إلى تلاشي فلسفة الحياة المنسجمة بالعالم. وتلاشي خُلق عملية الحفاظ، وضياع الحكمة المحلية، وتلاشى الهوية وفساد الرأسمال الإجتماعي.  Abstrak: Masyarakat dan kebudayaan manusia di manapun pada dasarnya selalu  berada dalam keadaan berubah. Perbedaannya ada yang berlangsung secara lambat, cepat, atau bahkan melalui proses evolusi dan revolusi. Salah satu faktor yang mempercepat proses perubahan sosial adalah intervensi pemerintah. Kajian ini bertujuan menguraikan perubahan sosial pada komunitas Suku Bajo sebagai akibat masuknya berbagai program pemerintah di pesisir Teluk Tomini. Penelitian ini menggunakan strategi sosiologi sejarah (historical sociology). Jenis data yang terkumpul berupa data primer dan data sekunder, yang dianalisis dengan menggunakan pendekatan kualitatif. Hasil kajian menunjukkan bahwa berbagai program pemerintah di pesisir Teluk Tomini, berupa penetapan kawasan konservasi, serta pemberian izin konsesi kepada swasta melalui Hak Pengusahaan Hutan (HPH), Hak Guna Usaha (HGU), dan usaha tambak telah menyebabkan hilangnya akses komunitas Suku Bajo terhadap sumber daya pesisir dan laut. Intervensi berbagai program pemerintah tersebut berimplikasi resettlement bagi komunitas Suku Bajo, sehingga menyebabkan terbelahnya komunitas Suku Bajo menjadi Bajo laut dan Bajo darat. Hilangnya akses Suku Bajo terhadap sumber daya pesisir dan laut, menyebabkan kelembagaan adat semakin melemah yang mengakibatkan memudarnya falsafah hidup selaras dengan alam, memudarnya etika konservasi, hilangnya kearifan lokal, hilangnya identitas diri, dan hancurnya modal sosial.